Design of Variable Amplitude Flapping Wing Aircraft and Realization of Multiple Flight Modes - Yueyang Hou; Yu Hou; Wei Sun; Kun Wang; Qiang Wang (Jixie chuandong)
Aiming at the problems of the single flight mode and inflexible flight attitude，a variable amplitude flapping wing aircraft is designed. By adjusting the flapping amplitude， the flapping wing motion attitude and flight mode can be switched. The kinematics model of flapping wing mechanism with variable amplitude is established to analyze the kinematic characteristics of flapping wing mechanism based on the joint simulation of Adams and Matlab. The aerodynamic model of flapping wing with multiple flight modes is established to analyze the aerodynamic characteristics of flapping wing mechanism with variable amplitude by XFLR5 software. According to set relevant parameters， various flight modes such as take-off， fast flight and slow cruise have been realized and the flexibility of flapping wing aircraft is improved， which provides a research basis for the further development of flapping wing aircraft in the future.